REGULATION ANALYSIS IN THE PROTECTION OF CULTURAL HERITAGE IN MEDAN CITY (STUDY OF MEDAN CITY CULTURAL SERVICE) - Ridho Zikrillah; Ismed Batubara (Fox Justi : Jurnal Ilmu Hukum, 2022)
An urban area needs to pay attention to historical heritage as an effort to utilize resources in the spatial dimension to achieve a better urban area. Historic buildings are one sourcae of income to increase foreign exchange through foreign tourist visits. Preservation of historic buildings in areas in Medan City is a very appropriate step to be implemented. Preservation of buildings has the aim of saving the preservation of objects that still survive today. From several cases we find a fact that often historical buildings are decreasing and being replaced with more modern buildings. For this reason, it is necessary to immediately preserve and protect it. Based on this, the author is interested in researching it and it is stated in the title "Analysis of Regulations in the Protection of Cultural Heritage in the City of Medan (Study of the Medan City Cultural Service)". The purpose of writing this scientific paper is to determine the role of the City Government and the Sumatran Heritage Agency (BWS) in the preservation of historic buildings in the city of Medan. While the expected benefits are as input for individuals and institutions who care about historic buildings. The research method used is descriptive qualitative method. by using the purposive technique, namely the determination of deliberately determined informants who are considered to know about the existence of historic buildings in the city of Medan, namely the employees of the Medan City Culture service, the Sumatran Heritage Agency, historians, and several owners of historic buildings in the city of Medan. The research location is the Medan City Cultural Service and the Sumatran Heritage Agency. From the results of data analysis, it can be concluded that the preservation of historic buildings that the actions that must be taken are 1) protection, 2) maintenance and 3) documentation of the historic building. The government's role in preserving historic buildings is: efforts to provide funds for the preservation of historic buildings, the establishment of a City Conservation Council, the formulation of a clear and firm legal basis. Meanwhile, the role of BWS is to propose a revision of Regional Regulation No. 6 of 1988 concerning Building Protection to the Medan City Government, as well as conducting field tests on the issue of preserving cultural heritage in good governance